Examination of Teachers' Professional Motivation and Technostress Levels - Akman, Emrah; Durgun, Burçin (Fırat University, 2022)
This study aimed to investigate the motivation and technostress levels of teachers and explore whether there is a relationship between these variables. A relational survey model was used in the research. The study group consisted of 455 teachers. Personal Information Form, Teacher Professional Motivation Scale, and Techno-stress Levels Defining Scale were used to collect the study's data. The research data were collected with Google Forms over five days in the fall semester of the 2021-2022 academic year. According to the findings, the professional motivation and technostress levels of teachers could differ according to variables such as gender, age group, type of faculty graduated, and branch. The study indicated that there was a negative relationship between teachers' motivation levels and technostress levels. Further research is recommended to investigate why the motivation of the faculty of arts and sciences graduates is higher than the teachers who graduated from the faculty of education. In addition, it is suggested that new studies can be conducted on the factors affecting teachers' technostress levels. It has been suggested to carry out new studies to reduce the technostress levels of teachers.

Bu araştırmada, öğretmenlerin meslekî motivasyon ve teknostres düzeylerinin belirlenmesi ve değişkenler arasındaki ilişki durumunun saptanması amaçlanmıştır. Çalışmada genel tarama modellerinin içinde yer alan ilişkisel model kullanılmıştır. Çalışma grubunda 455 öğretmen yer almaktadır. Araştırmanın verilerini toplama aşamasında Kişisel Bilgi Formu, Öğretmen Meslekî Motivasyonu Ölçeği ve Öğretmenlerin Teknostres Düzeylerini Belirleme Ölçeğinden yararlanılmıştır. Araştırmanın verileri Google Formlar ile 2021-2022 eğitim yılının güz döneminde beş günde toplanmıştır. Araştırma sonuçlarına göre; öğretmenlerin meslekî motivasyon ve teknostres düzeylerinin cinsiyet, yaş grubu, teknoloji kullanımıyla ilgili hizmet için eğitim alma durumu, teknoloji kullanma seviyesinin yeterli ya da yetersiz olma durumu, okulda ihtiyaç duydukları teknolojiye erişebilme durumu, mezun olunan fakülte türü, branş gibi değişkenlere göre farklılık gösterdiği saptanmıştır. Araştırmada öğretmenlerin meslekî motivasyon düzeyleri ile teknostres düzeyleri arasında negatif yönde zayıf bir ilişki olduğu görülmüştür. Fen-Edebiyat Fakültesi mezunu olan öğretmenlerin meslekî motivasyonlarının Eğitim Fakültesi mezunu olan öğretmenlere daha yüksek olmasının sebeplerinin araştırılması ve öğretmenlerin teknostres düzeylerini azaltmak amacıyla yeni çalışmalar yapılması önerilmiştir.
ÖĞRETMENLERİN MESLEKÎ MOTİVASYON VE TEKNOSTRES DÜZEYLERİNİN İNCELENMESİ